2017
DOI: 10.1080/15366367.2017.1392821
|View full text |Cite
|
Sign up to set email alerts
|

Talk and Gesture as Process Data

Abstract: This paper examines the topic of talk and gesture in computer-based tests, and what it can tell us about assessment performance. The paper describes a micro-analytic approach, and uses video-ethnographic methods to investigate data that is not captured by conventional assessment scores or by computer-generated log files. The paper presents transcripts from assessment events in the OECD Adult Skills Survey (PIAAC) in Slovenia. The transcripts describe a three-way interaction between interviewer, respondent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Another strategy for supporting the interpretation of a process indicator derived from log data is to triangulate it with other methods and data sources obtained from a particular cognitive assessment. Here, the process indicator is related to other measures of the same attribute of the work process, for instance, measures based on think-aloud protocols, eye-tracking or video recordings of the test-taker and the screen (Maddox, 2017). These additional measures should already be validated to some extent and interpretable in terms of the target attribute.…”
Section: Nomothetic Spanmentioning
confidence: 99%
“…Another strategy for supporting the interpretation of a process indicator derived from log data is to triangulate it with other methods and data sources obtained from a particular cognitive assessment. Here, the process indicator is related to other measures of the same attribute of the work process, for instance, measures based on think-aloud protocols, eye-tracking or video recordings of the test-taker and the screen (Maddox, 2017). These additional measures should already be validated to some extent and interpretable in terms of the target attribute.…”
Section: Nomothetic Spanmentioning
confidence: 99%
“…Empirical research has shown that in combination with response patterns, RTs can lend valuable insight into interesting test-taker, item and test characteristics, such as pre-knowledge of items, motivation, time-pressure or differential speededness (Bridgeman and Cline, 2004; Wise and Kong, 2005; Meijer and Sotaridona, 2006; van der Linden et al, 2007; van der Linden and Guo, 2008; Marianti et al, 2014; Qian et al, 2016). New types of process data have been explored lately that carry the potential to lend additional insight into (latent) response processes and to improve inferences about constructs of interest (e.g., Azevedo, 2015; He et al, 2016; Goldhammer and Zehner, 2017; Maddox, 2017). To make valid inferences from process data, innovative joint models are needed that are capable of utilizing test-taker data beyond RAs and RTs, while accounting for complex relationships in multiple data types.…”
Section: Introductionmentioning
confidence: 99%
“…The method that informs this paper is microethnographic as its concern is with faceto-face interaction (talk and gesture) in real-life testing situations rather than the wider social and institutional context of the assessment (see Maddox, 2015;Maddox, 2017). The approach can be described as inductive since it seeks to observe social phenomenon, and to identify patterns that can inform explanation and the development of hypotheses.…”
Section: Methodsmentioning
confidence: 99%
“…Observing testing situations produces detailed process data on real-life assessment practice (Maddox and Zumbo, 2017;Maddox, 2017). This includes ethnographic descriptions of talk and gesture, located in the wider context of the testing situation.…”
Section: Methodsmentioning
confidence: 99%